2019
DOI: 10.1002/cncr.32598
|View full text |Cite
|
Sign up to set email alerts
|

Pan‐cancer clinical and molecular analysis of racial disparities

Abstract: Background Racial disparities in cancer outcomes are increasingly recognized, but comprehensive analyses, including molecular studies, are limited. The objective of the current study was to perform a pan‐cancer clinical and epigenetic molecular analysis of outcomes in African American (AA) and European American (EA) patients. Methods Cross‐platform analyses using cancer databases (the Surveillance, Epidemiology, and End Results program database and the National Cancer Data Base) and a molecular database (The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Histology alone, however, does not account for the worse survival of Black endometrial cancer patients. A study of data from the Surveillance, Epidemiology and End Results (SEER) program showed that Black in comparison with White patients had worse survival in every histologic category, stratified by stage, grade and age [ 16 , 22 ]. This study also found that rare aggressive tumor types accounted for a higher percentage of the deaths in Black (53%) compared with White (36%) patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histology alone, however, does not account for the worse survival of Black endometrial cancer patients. A study of data from the Surveillance, Epidemiology and End Results (SEER) program showed that Black in comparison with White patients had worse survival in every histologic category, stratified by stage, grade and age [ 16 , 22 ]. This study also found that rare aggressive tumor types accounted for a higher percentage of the deaths in Black (53%) compared with White (36%) patients.…”
Section: Resultsmentioning
confidence: 99%
“…Pathway analysis of the SEER program database from 2000 to 2015 in patients classified as European-American or African-American was performed to determine the clinical significance and biologic functions of the differentially expressed miRNAs related to cancer type [ 22 ]. They reported that differentially expressed miRNAs were associated with cancer drug resistance pathways through cancer drug efflux for all cancer types including uterine.…”
Section: Resultsmentioning
confidence: 99%
“…The main focus of the present study was miR-130a-3p, which has been found to be differentially expressed in different tumors, including breast cancer and non-small cell lung cancer ( 11 , 12 ). In addition, increased miR-130-3p levels have also been found in TC tissues ( 13 ). However, whether miR-130-3p is dysregulated in the exosomes of patients with DTC has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…To address this, several studies investigated molecular differences within TNBC tumors of African-American and European-American patients. TNBC tumors of African-American women were shown to display enrichment of gene sets related to a high proliferative rate, high genomic grade index, BRCA1 deficiency, increased activation of insulin-like growth factor 1 receptor, and increased angiogenesis, closely resembling the basal like-1 TNBC subtype gene signature as described by Lehmann et al 23,[28][29][30][31][32][33] . In addition, it has been suggested that an abundance of cancer stem cells might, in part, contribute to the worse survival of African-American women with TNBC tumors [34][35][36][37][38] .…”
Section: Introductionmentioning
confidence: 76%